Efficiency Analysis of Flood Mitigation Policies in North Sumatra in 2025: An Economic Analysis of Law Perspective - Riri Rezeki Hariani; Muhammad Arif Nasution; Muhammad Sutan Agung; Ira Thania Rasjidi; Arifin Saleh; Muhammad Fathin Abdul Fachri (Journal of Creative Power and Ambition (JCPA), 2026)
Floods are one of the most frequent hydrometeorological disasters in North Sumatra Province and have significant impacts on social life, the economy, and regional development. Throughout 2025, the North Sumatra Regional Disaster Management Agency (BPBD) recorded 623 disaster events, with 122 incidents involving floods spread across various regencies/cities. The high frequency of floods raises questions about the effectiveness and efficiency of disaster management policies implemented by the local government. This study aims to analyze the efficiency of flood management policies in North Sumatra in 2025 using an Economic Analysis of Law perspective. The research method used is normative juridical with a statutory regulatory approach and a conceptual approach. The results show that flood management policies in North Sumatra have an adequate legal basis, but still face various obstacles in implementation, particularly related to efficient budget use, institutional coordination, and optimization of prevention-based mitigation. Based on the Economic Analysis of Law perspective, policies oriented towards mitigation and disaster risk reduction are more efficient than policies that only focus on post-disaster management. Therefore, it is necessary to reconstruct policies that prioritize the principles of economic efficiency, reducing social costs, and increasing community resilience to flood disasters.